COMMON MISTAKES IN ENGLISH PREPOSITIONS AND HOW TO AVOID THEM - Marjona Esojonova (Ustozlar uchun, 2025)
This essay discusses ten common mistakes learners make when using English prepositions. It highlights errors related to time expressions, purpose, location, verb-preposition combinations, and more. Each mistake is explained with examples and tips to avoid them. The essay emphasizes the importance of practice and understanding to use prepositions correctly and enhance communication skills in English.